Mn‐superoxide dismutase activity is associated with orofacial involuntary movements in schizophrenia patients with tardive dyskinesia. (January 2015) - Wu, Jing Qin; Chen, Da Chun; Tan, Yun Long; Soares, Jair C.; Zhang, Xiang Yang
<x xml:space="preserve">Abstract</x> Background Oxidative stress‐induced damage may be involved in tardive dyskinesia (TD) development. Superoxide dismutase (SOD), the key antioxidant enzyme, was found abnormal in TD. Objective We examined the role of oxidative stress in relation to TD and TD subtypes in schizophrenia using manganese SOD (MnSOD) as the biomarker. Methods We recruited 152 male chronic patients with (n = 76) and without TD (n = 76) meeting Diagnostic and Statistical Manual of Mental Disorders‐IV criteria for schizophrenia and 75 male control subjects. We examined the MnSOD activity for all subjects. Positive and Negative Syndrome Scale and the Abnormal Involuntary Movement Scale (AIMS) were assessed in the patients. Results Manganese SOD activity was lower in patients with TD than non‐TD (p < 0.05). In the patients with TD, orofacial and total scores of AIMS were positively associated with MnSOD levels (both p < 0.05). Multiple regression analysis further confirmed that MnSOD was an independent contributor to both the orofacial and the total scores of AIMS (both p < 0.05). Conclusions Oxidative stress reflected by compromised oxidative defense may play a role in the development and severity of TD. There may be an etiologic relationship between increased SOD level and dyskinetic movements associated with TD. In particular, MnSOD activity may have a specific role in orofacial TD. Copyright © 2014 John Wiley & Sons, Ltd.